2014
DOI: 10.1002/ajh.23643
|View full text |Cite
|
Sign up to set email alerts
|

Automated screening for myelodysplastic syndromes through analysis of complete blood count and cell population data parameters

Abstract: The diagnosis of myelodysplastic syndromes (MDS) requires a high clinical index of suspicion to prompt bone marrow studies as well as subjective assessment of dysplastic morphology. We sought to determine if data collected by automated hematology analyzers during complete blood count (CBC) analysis might help to identify MDS in a routine clinical setting. We collected CBC parameters (including those for research use only and cell population data) and demographic information in a large (>5,000), unselected sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…Further, in contrast to previous classifiers utilizing SuperPC analysis, we used a random forest method to exploit the robust properties of ensemble machine learning methods (26). We recently obtained robust classification results using a random forest classifier to segregate myeloid neoplasms from reactive conditions (27) and wished to utilize a similar approach for AML survival prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in contrast to previous classifiers utilizing SuperPC analysis, we used a random forest method to exploit the robust properties of ensemble machine learning methods (26). We recently obtained robust classification results using a random forest classifier to segregate myeloid neoplasms from reactive conditions (27) and wished to utilize a similar approach for AML survival prediction.…”
Section: Resultsmentioning
confidence: 99%
“…10–16 In hematology, machine learning methods applied to analyzing automated complete blood count parameters have been used to accurately identify patients with myelodysplasia. 17 Software is actively being developed that provides the next level of “logistical computational” software, interfaces, and tools that allow user-friendly movement of next-generation sequencing files and data sets through instruments and the bioinformatics pipeline to the laboratory information system; between the laboratory information system and online curated data sources that allow a pathologist to generate an accurate and up-to-date report; and from the laboratory information system to the EHRs as both human-readable and computationally mineable data. 11,12,18,19 In addition, computational quality assurance and quality control tools are being incorporated into the analysis of these large and multidimensional data sets to ensure that the data meet quality standards.…”
Section: Key Conclusion: the Impact Of Computational Pathology On CLmentioning
confidence: 99%
“…The gold standard for myelodysplasia diagnosis is careful microscopic observation by an experienced hematologist or hematopathologist [1,2,[5][6][7], but this procedure may be dependent on the subjectivity of the respective observer, with interobserver variation in the obtained results [7,9,10]. On the other hand, we and other investigators reported that the characteristic neutrophil distribution pattern obtained using automated hematology analyzers such as Coulter LHseries, Sysmex XE-2100, or CELL-DYN SAPPHIRE could be a convenient as well as objective finding for peripheral blood dysgranulopoiesis in patients with MDS [11][12][13][14][15]. These investigators evaluated hematology analyzers capable of flow cytometry (FCM) for 5part white blood cell differentials .…”
Section: Introductionmentioning
confidence: 98%